Schizophrenia : A Brother Finds Answers in Biological Science - Chase, Ronald (Book collections on Project MUSE., 2013)
Painful and often misunderstood, schizophrenia profoundly affects people who have the disease and their loved ones. Here Ronald Chase, an accomplished biologist, sets out to better understand what happened to his older brother, Jim, who developed schizophrenia as a young adult. In a fiercely loyal and honest memoir, Chase uses scientific exploration to find answers to deeply personal questions about the course of his brother's illness.